4-H Youth Development Programming in Indigenous Communities: A Critical Review of Cooperative Extension Literature - Joshua Farella; Mike Hauser; Amy Parrott; Joshua D. Moore; Meghan Penrod; Jeremy Elliott-Engel ([TEST] Journal of Extension, 2021)
A literature review was conducted using the key words relating to Native American Youth and 4-H to assess the current state of 4-H youth programming serving First Nation/ Indigenous populations to inform future Extension initiatives. A systematic and qualitative review determined what level of focus the conducted programming efforts placed on broadly accepted elements of cultural identity as noted in the Peoplehood Model. A very small number of articles (N=13) were found pertaining to 4-H and Indigenous Communities. Fewer demonstrated emphasis on the peoplehood elements of language, place, traditional ceremony or calendars, and history. This work investigates a continuing inequity in 4-H PYD–both in service and reporting–and suggests some next steps for creating a more inclusive 4-H program for Native American/First Nation/Indigenous youth.
Keywords: indigenous; American Indian/Alaska Native; Peoplehood Model; 4-H; Indian Country; Tribal Extension Programs